An Experimental Comparison of Two Self-Report Methods for Measuring Lambda - Horney, Julie (Journal of research in crime and delinquency, 1992)
Presents the use of RAND method in measuring crime rates and the month-by-month reporting method in interviewing prison inmates to measure crime rates in terms of lambda. How the RAND has generated much interest and controversy; Comparison of results between RAND and month-by-month method; Differences of RAND (control condition) and month-by-month method (experimental condition); Computation of lambda for the control and experimental group; Conclusions